Intra vitam lumbar cerebrospinal fluid and serum and postmortem ventricular immunoreactive apolipoprotein E in patients with Alzheimer's disease. Issue 4 (April 1996) - Rösler, N; Wichart, I; Jellinger, K A
Abstract : Using a specific enzyme linked immunosorbent assay (ELISA) method, total apolipoprotein E immunoreactivity (tApoE-IR) was measured in premortem lumbar CSF and serum of patients with "probable" Alzheimer's disease and in postmortem ventricular CSF of patients with Alzheimer's disease confirmed by necropsy. Concentrations were compared with those from patients with other neurological diseases and controls. The mean serum:lumbar CSF ratio of ApoE-IR was 15.9 suggesting that the main portion of lumbar ApoE-IR is synthesised intrathecally. No significant differences in ApoE-IR between patients with Alzheimer's disease and the other groups were detected in either CSF compartment. In lumbar CSF, there was no correlation between ApoE-IR of patients with Alzheimer's disease and their mini mental state scores. These results suggest that the diagnostic value of ApoE-IR measurements in CSF of patients with Alzheimer's disease as a single determination is less than that of other markers, in particular tau protein. On the other hand, ApoE determinations could be useful as part of a neurochemical profile of Alzheimer's disease.